Subthalamic nucleus stimulation and levodopa modulate cardiovascular autonomic function in Parkinson’s disease - Kai Li; Rocco Haase; Heinz Rüdiger; Manja Reimann; Heinz Reichmann; Martin Wolz; Tjalf Ziemssen (Scientific Reports, 2017)
Abstract We aimed to explore the effects of bilateral subthalamic nucleus stimulation and levodopa on cardiovascular autonomic function in Parkinson’s disease. Twenty-six Parkinson’s disease patients with bilateral subthalamic nucleus stimulation in a stable state were tested under stimulation off and dopaminergic medication off (OFF-OFF), stimulation on and dopaminergic medication off (ON-OFF), and stimulation on and medication (levodopa) on (ON-ON) conditions by recording continuously blood pressure, ECG, and respiration at rest, during metronomic deep breathing, and head-up tilt test. Thirteen patients were diagnosed as orthostatic hypotension by head-up tilt test. Baroreflex sensitivity and spectral analyses were performed by trigonometric regressive spectral analysis. Subthalamic nucleus stimulation and levodopa had multiple influences. (1) Systolic blood pressure during tilt-up was reduced by subthalamic nucleus stimulation, and then further by levodopa. (2) Subthalamic nucleus stimulation and levodopa had different effects on sympathetic and parasympathetic regulations in Parkinson’s disease. (3) Levodopa decreased baroreflex sensitivity and RR interval only in the orthostatic hypotension group, and had opposite effects on the non-orthostatic hypotension group. These findings indicate that subthalamic nucleus stimulation and levodopa have different effects on cardiovascular autonomic function in Parkinson’s disease, which are modulated by the presence of orthostatic hypotension as well.